1967
DOI: 10.1017/s0022112067001132
|View full text |Cite
|
Sign up to set email alerts
|

The perturbed region behind a diffracting shock wave

Abstract: The results of an experimental study of the diffraction of shock waves on plane-walled convex corners are given for a Mach number range from 1·0 to 5·0. The behaviour of the disturbances produced in the region perturbed by the corner are discussed. It is shown that the position of the slipstream and tail of the Prandtl-Meyer fan, and the velocities of the contact surface and second shock become independent of corner angle for angles greater than 75°. Comparisons with theoretical predictions of Jones, Martin &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 4 publications
7
52
0
2
Order By: Relevance
“…It can be noted that the occurrence of the lambda shock is not affected by the presence of the coflow shear layer. From Skews [6], in a quiescent gas, multiple lambda shocks are observed on the shear layer for Mach numbers 1.4 to 1.5. In the present flow configuration a single lambda shock occurs, in agreement with previous findings.…”
Section: Ramp Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…It can be noted that the occurrence of the lambda shock is not affected by the presence of the coflow shear layer. From Skews [6], in a quiescent gas, multiple lambda shocks are observed on the shear layer for Mach numbers 1.4 to 1.5. In the present flow configuration a single lambda shock occurs, in agreement with previous findings.…”
Section: Ramp Geometrymentioning
confidence: 99%
“…The flow features that characterise the shock wave diffraction without co-flow have been analysed with incident shock Mach numbers in the range of 1.0 to 5.0 [6]. However, the complexity of the flow scenario and the small time scales have made the capture and analysis of the processes quite challenging.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study, Skews [25] obtained schlieren images that identified the features of the flow. An unsteady expansion fan is generated at the corner.…”
Section: Jet Formation Time Scalesmentioning
confidence: 99%
“…Within this region the existence of various disturbances can be postulated or have I been identified experimentally (e.g. Skews, 1967aSkews, , 1967bBazhenova et al, 1971). The initial expansion is a truly steady region, turning the fluid to the appropriate separation angle for the vortex sheet at A.…”
Section: Strong Shock Diffractionmentioning
confidence: 99%